Editorial - Ząbkowicz, Anna; Pietrzak, Michał; Jurczuk, Anna (Social Entrepreneurship Review, 2023)
The editorial a special issue focusing on how economists employ institutionalism. Institutionalism is increasingly recognized as essential for addressing practical and political challenges.